Scenario of Retinoblastoma Among Bangladeshi Children – A Single Center Experience of 10 Years - Rani Roy, Soma; Nuruddin, Murtuza; Asgar, Ali (BOHR International Journal of Current Research in Optometry and Ophthalmology, 2022)
Background: Retinoblastoma is the most common intraocular tumor of childhood and most detected cases are from Indian subcontinent. Here we explore the presentation of retinoblastoma with its histopathological features and treatment outcome in a tertiary eye care center in Bangladesh. Method: This was a retrospective study of 70 eyes of 60 patients in a ten years period from 2006 to 2016 who had met the criteria regarding demographic profile, clinical presentation, management and histopathology. Tumor was classified based on IIRC (International Intraocular Retinoblastoma Classification) for intraocular tumor and IRSS (International Retinoblastoma Staging System) for extraocular tumor by reviewing the data revealed from EUA, imaging and histopathology. Result: The mean age of presentation was (Table 1) 31.3 ± 21.68 months, range was 4 months to 96 months and the most frequent presenting age was 12 months. Fifty three percent of children presented between 13 months and 59 months. Mild male predominance was 53.3% (n = 32). Unilateral cases were 71.3% (n = 43) and 6.7% (n = 4) of patients had positive family history. The most common presenting sign was leucocoria (85%) followed by strabismus (18.3%) and proptosis (13.3%). Fifty five (91.6%) children presented with intraocular tumor and 64.9% were with Group E. Enucleation (91.6%) was the prime treatment modality and histopathological risk factor was positive in 51.7% cases among 63.3% cases of primary enucleation. Fifty percent of treated children were in regular follow up. Conclusion: Most children presented delayed and prime treatment modality was enucleation. Only half of the patients were in regular follow up. Generation of awareness, proper referral, information regarding treatment availability and early detection of cases can increase the survival rate and globe salvage.